1991
DOI: 10.1213/00000539-199107000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Responses to Endotracheal Extubation After Coronary Artery Bypass Grafting

Abstract: After coronary artery bypass grafting (CABG) surgery, patients may remain at risk for myocardial ischemia and infarction and ventricular dysrhythmias. The hemodynamic responses to endotracheal extubation and the efficacy of intravenous lidocaine pretreatment were studied after CABG surgery and overnight mechanical ventilation. Twenty-five patients were divided into two groups: group 1 (n = 13) patients who had tracheal extubation after pretreatment with a placebo; group 2 patients who received lidocaine (1 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 0 publications
2
19
0
1
Order By: Relevance
“…This finding implies that the patients who had lower CI developed DVWR. This finding is consistent with past literature that reported an alteration in cardiac index during weaning was found to have association with weaning failure (15,(76)(77)(78). However, the logistic prediction model revealed that CI is not a significant antecedence to predict the DVWR after CABG surgery.…”
Section: Cardiac Index and Dysfunctional Ventilator Weaning Response:supporting
confidence: 92%
“…This finding implies that the patients who had lower CI developed DVWR. This finding is consistent with past literature that reported an alteration in cardiac index during weaning was found to have association with weaning failure (15,(76)(77)(78). However, the logistic prediction model revealed that CI is not a significant antecedence to predict the DVWR after CABG surgery.…”
Section: Cardiac Index and Dysfunctional Ventilator Weaning Response:supporting
confidence: 92%
“…Though tracheal extubation seems to be a benign procedure, multiple studies have shown that it can cause significant increase in BP and HR which may persist till the recovery period. [1][2][3][4][5][6] High degree of sympathetic stimulation, as evidenced by tachycardia, hypertension and increased levels of circulating catecholamines during extubation may prove to be detrimental to their health or to the successful outcome of surgery.Hypertensive subjects exhibit an exaggerated response to laryngoscopy and intubation as well as to awakening and extubation compared to normotensive patients. 7,13,45 Increase in BP, HR and RPP which is a multiple of SBP and HR increases the cardiac workload and the oxygen demand of the myocardium; increasing the risk of developing a fresh episode of myocardial ischemia and infarction in known patients of ischemic heart disease due to a fixed coronary blood flow, along with fall in cardiac index and ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative extubation of trachea is an important event in the course of general anaesthesia which causes a modest (10% to 30%) and transient (lasting approximately 5 to 15 minutes) increase in the HR and BP. [1][2][3][4][5][6][7] Normally these responses are transient in nature hence well tolerated by normotensive healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…60 After coronary artery bypass surgery, these changes tend to be transient, lasting 5 to 10 minutes, and they usually are not associated with electrocardiographic evidence of myocardial ischemia. 61 Coronary sinus lactate extraction measurements, however, indicate that among patients with poor cardiac function, extubation may be associated with myocardial ischemia. 62 Patients with inadequately controlled hypertension, carcinoid, pheochromocytoma, hypertension associated with pregnancy, or hyperthyroidism may be expected to display even greater increases in blood pressure in response to tracheal extubation.…”
Section: Hypoventilation Syndromesmentioning
confidence: 99%